Review of Smart Antenna Approaches in Wireless Systems - Anand, C. (IRO Journal on Sustainable Wireless Systems, 2023)
Wireless mobile communication is one of the rapidly growing fields of Information and Communication Technologies (ICT). The adoption of smart antennas will also minimize the cost. The success of smart antennas relies on two phases: In first phase, the features of smart antennas should be considered in design phase of next-generation wireless mobile communication systems. In second phase, the performance of smart antennas should be analyzed according to crucial parameters that satisfy the requirements of next-generation wireless mobile communication systems. The proposed research study summarizes the concept and types of smart antennas. Further, the most recent innovations in smart antenna domains such as varying network conditions, coverage & connectivity, Quality of Service (QoS), energy efficiency, routing are discussed.